The Influence of Education Using The Android Based Mom Smile Application on Pregnant Women’s Knowledge About Pregnancy Gingivitis - Nabila safir; Ratih Larasati; Silvia Prasetyowati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Pregnancy gingivitis remains a prevalent oral health problem among pregnant women, largely driven by hormonal changes and inadequate awareness of proper oral hygiene practices. Despite its high prevalence and potential complications, including heightened risks of adverse pregnancy outcomes, educational resources tailored to improving oral health knowledge during pregnancy are still limited and often ineffective. This study addresses this gap by examining the impact of the Android-based Mom Smile application as an accessible digital learning tool for enhancing pregnant women’s knowledge of pregnancy gingivitis. This research employed a quasi-experimental one-group pretest–posttest design involving 32 pregnant women attending the Gayam Health Center in Sumenep Regency. Participants completed a validated knowledge questionnaire assessing their understanding of pregnancy gingivitis including its definition, symptoms, causes, impacts, and prevention before and after engaging with the Mom Smile application. Data were analyzed using the Wilcoxon signed-rank test due to non-normal distribution. The findings demonstrated a substantial improvement in knowledge following the intervention. The mean knowledge score increased from 54.68% in the pretest to 83.28% in the posttest. Prior to the intervention, 62% of participants exhibited low knowledge levels, whereas after using the application, 88% achieved high knowledge levels. Statistical analysis confirmed a significant difference between pretest and posttest scores (p < 0.05), indicating the effectiveness of the Mom Smile application. In conclusion, the Mom Smile application proved to be an effective digital educational tool for enhancing pregnant women’s knowledge about pregnancy gingivitis. Its motion-graphic–based content offers an engaging and practical alternative to traditional printed materials. Integrating such digital health education into antenatal care services may support better oral hygiene practices, thereby contributing to improved maternal health outcomes.